MANAJEMEN PENGELOLAAN USAHA YANG EFISIEN PADA UD PERSADA UNGARAN - Harminingtyas, Rudika; Widowati, Maduretno; Adhi, Daniel Kartika (Fokus ABDIMAS, 2022)
UMKM serve as both the pillar and the driving force of the nation's economy. Additionally, there are a sizable number of UMKM in each region, and they can thrive in any economic climate. But they largely rely on gut feeling or business intuition to run their company, paying little attention to managerial issues. excellent and effective Counseling is therefore necessary, like at UD Persada Ungaran, a company that makes socks. The three components of extension are management, marketing, and technological issues. After counseling, UD Persada Ungaran employees responded favorably, and their abilities improved.Keyword: Counseling,Effcient management